"New Protectionism" in ASEAN. Issue 1 (2nd January 2020) - Devadason, Evelyn S.
ABSTRACT: The 21st century suggests a somewhat vexing scenario of "new protectionism", especially with the rise of protectionist non-tariff measures or NTMs. This largely refers to standard-like NTMs (sanitary and phytosanitary measures and technical barriers to trade, known as SPS and TBTs respectively) with a dual purpose of non-trade policy objectives and (hidden/concealed) protectionism. Since ASEAN is a high user of standard-like NTMs relative to other measures, this begs the question if there is an intentional shift toward murky protectionism in the region. Grounded on a few criterion to establish potential protectionism, the paper forwards the plausibility of "hidden" barriers in the standard-like NTMs drawing upon related secondary data, and specific illustrative cases of harmful and burdensome NTMs in the individual ASEAN countries. From the narrative experiences of ASEAN, it is inferred that procedural obstacles, directly associated with a reported standard-like NTMs, instead of the NTM itself, account for the "hidden" barriers in ASEAN. The paper concludes that irrespective of the motivation for protectionist NTMs, whether unintentional or intentional, procedural obstacles deserve attention in their own right. Regulatory reform for the standard-like NTMs is therefore needed at the national-level of the AMS to get rid of those "hidden" barriers.